The Cultural Cold War as Battlefield- the case of Saunder’s The CIA and the World of Arts, James Bond and Songs - Ikram Khechai (My University, 2019)
IV Abstract: This dissertation sheds light on one influential aspect of the Cold War that is the cultural one. In addition to political and economic propaganda, the cold war was waged on important cultural propaganda fronts that proved its effectiveness and appeared to be more powerful than other weapons used in a real battlefield. It studies the Cultural weapons in Saunders’ the CIA and World of Arts and Letters, analyses James Bond novels and movies and highlights their contribution to the cold war in addition to the reflection of the cold war through songs. It also stresses the importance of expanding studies of the cold war beyond the traditional explanatory value of geopolitics boundaries to a cultural cold war study and explains the efforts made to utilize propaganda and culture as a successful strategy in the battle of hearts and mind.
Keywords: Key words: cold war, culture, propaganda, novels, movies, songs, weapons.